Fast line, arc/circle and leg detection from laser scan data in a player driver - Xavier, J. (2013)
A feature detection system has been developed for real-time identification of lines, circles and people legs from laser range data. A new method sutable for arc/circle detection is proposed: the Inscribed Angle Variance (IAV). Lines are detected using a recursive line fitting method.